1978
DOI: 10.1007/bf00427187
|View full text |Cite
|
Sign up to set email alerts
|

Identification of soluble fibrinogen fibrin monomer complexes by non-enzymatic polymerisation in the tissue

Abstract: In states of plasmic hypercoagulability and consumption coagulopathy ethanol favours the non-enzymatic polymerization of circulating soluble fibrinogen fibrin monomer complexes (FFMC) in vitro. The ethanol-gelation test of Godal and Abildgaard makes use of this phenomenon, called paracoagulation. The present studies show that it is also possible to visualize soluble FFMC by means of ethanol-gelation. In the electron microscope, FFMC, polymerized non-enzymatically by ethanol in the spleen, are characterized by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

1981
1981
2008
2008

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
4
0
1
Order By: Relevance
“…Systematic investigations on the ultrastructure demonstrated, however, that the fibrinogen derivatives adsorbed on the surface of the RES cells are only partly characterized by myceloid fibrillar precipitates with the axial periodicity of 23 nm. Furthermore, fibrillar bundles became visible, consisting of filaments with irregularly sized spheric bodies, arranged in chains [15]. Residues of filamentary structures with a transverse striation and a rhythmic axial periodicity, characteristic of fibrin, were only occasionally seen between the spheric precipitates.…”
Section: Fibrin Monomer and Fibrin Oligomermentioning
confidence: 99%
See 3 more Smart Citations
“…Systematic investigations on the ultrastructure demonstrated, however, that the fibrinogen derivatives adsorbed on the surface of the RES cells are only partly characterized by myceloid fibrillar precipitates with the axial periodicity of 23 nm. Furthermore, fibrillar bundles became visible, consisting of filaments with irregularly sized spheric bodies, arranged in chains [15]. Residues of filamentary structures with a transverse striation and a rhythmic axial periodicity, characteristic of fibrin, were only occasionally seen between the spheric precipitates.…”
Section: Fibrin Monomer and Fibrin Oligomermentioning
confidence: 99%
“…Using fluorescein-labeled antifibrinogen antiserum, these fibrillar precipitates showed intensive secondary fluorescence. Electron microscopic studies of the ethanol-fixed paraffin sections [15] revealed fibrillar structures with a uniform transverse striation and an axial periodicity of 23 nm. This could not be demonstrated by fixation of the material with formalin.…”
Section: Fibrin Monomer and Fibrin Oligomermentioning
confidence: 99%
See 2 more Smart Citations
“…Hyaline Membranen als Korrelate der Hyperkoagulabilität (BLEYL et al 1978). Als Folge der Zellnekrosen in der Alveolarwand treten Fibrinmonomere respiratorischen Insuffizienz im Schock der Mikrothrombosierung und nachfolgender Perfusionsstörung die größte Bedeutung zugemessen werden muß.…”
Section: Mikrothrombose Mikroembolismusunclassified